2013
DOI: 10.1002/jhm.2090
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of written hospitalist sign‐outs in answering overnight inquiries

Abstract: Background Hospitalists are key providers of care to medical inpatients, and sign-out is an integral part of providing safe, high quality inpatient care. There is little known about hospitalist-to-hospitalist sign-out. Objective To evaluate the quality of hospitalist/physician-extender sign-outs by assessing how well the sign-out prepares the night team for overnight events and to determine attributes of effective sign-out. Design Analysis of a written-only sign-out protocol on a non-teaching hospitalist s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…All but 2 of the studies (95%) 24,35 were conducted to evaluate shift-to-shift handoffs in physicians in training. Academic medical centers appear to be conducting the majority of the research on handoffs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All but 2 of the studies (95%) 24,35 were conducted to evaluate shift-to-shift handoffs in physicians in training. Academic medical centers appear to be conducting the majority of the research on handoffs.…”
Section: Discussionmentioning
confidence: 99%
“…22,[24][25][26]28,29,35,[44][45][46][47][48][49][50][51][52] One study found that 92% of errors were committed in a core data element and could have been prevented with auto-population. 44 While many studies with process outcomes specifically showed fewer data omissions, 24,25,28,29,34,44-47,49-52 1 found that less than 50% included allergies or code status when using the electronic handoff system.…”
Section: Process Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Despite the routine use of written handoff tools as a reference by on-call physicians, 2 it is well known that they can be misleading to on-call providers, resulting in medical errors.…”
mentioning
confidence: 99%